Factors related to absenteeism of nurses at hospitals affiliated with Tehran Medical University - Hamidizadeh, S; Mohammadi, E; Fereydonimoghadam, M (Advances in Nursing & Midwifery, 2010)
Background and aim Absenteeism cause many problems for managers and other personnel especially nursing staff and leads to decreased quality and quantity of nursing care and, ultimately, health level of society. This descriptive study was conducted to determine the related factors of absenteeism in nursing staff at hospitals affiliated with Tehran Medical University. Materials and methods 105 registered nurses with at least 1 event of absenteeism at different healthcare centers of Imam Khomeini Hospital were randomly selected. A questionnaire in 3 parts including items for demographics, related factors of absenteeism and an open question asking about the ways to reduce it was used for data collection.Content and test-retest methods were used for validity and reliability of the tool respectively (r=0/87). Such statistical tests as Chi-square and t-student were used for data analysis. Findings Most subjects (9.82%) was between 26-39 (mean age=4.30±1.18); 6.78%, women; 6.88%, baccalaureate; 3.74%, married; 1.57% with rental residence and 4.71% with shift rotation. 5.65% considered therapeutic problems as the most effective factor in absenteeism, of which 9.83% named tiredness from work as a reason for them. A significant correlation was found between absenteeism and age as well as sex (P<0.05) and not educational level. Conclusion There are many reasons for absenteeism of nurses in different shifts; however, the most important ones include tiredness from work and dissatisfaction from their shifts. Accordingly, by considering available resources, capabilities and limitations, the most appropriate strategies can be applied in this regard. Keywords: Absenteeism, Shift, Nurse, Hospital. *Corresponding Author: Saeid, Hamidizadeh. Dept. of Nursing,Faculty of Nursing and Midwifery,Jahrom University of Medical. E-mail: hamidizadehs@yahoo.com